An automated analysis methodology to detect inconsistencies in web services with WSDL interfaces. (4th February 2011) - Fisher, Marc; Elbaum, Sebastian; Rothermel, Gregg
SUMMARY Web Service Definition Language (WSDL) is being increasingly used to specify web service interfaces. Specifications of this type, however, are often incomplete or imprecise, which can create difficulties for client developers who rely on the WSDL files. To address this problem a semi‐automated methodology that probes a web service with semi‐automatically generated inputs and analyzes the resulting outputs is presented. The results of the analysis are compared to the original WSDL file and differences between the observed behavior of the service and the WSDL specifications are reported to the user. The methodology is applied in two case studies involving two popular commercial (Amazon and eBay) web services. The results show that the methodology can scale, and that it can uncover problems in the WSDL files that may impact a large number of clients. Copyright © 2011 John Wiley & Sons, Ltd.